Methotrexate in the treatment of paediatric alopecia areata: Retrospective case series and updated meta‐analysis. (4th December 2019) - Phan, Kevin; Lee, Geoffrey; Fischer, Gayle
Abstract: Background/Objectives: There is a paucity of data regarding the efficacy and safety of methotrexate (MTX) in childhood alopecia areata (AA), particularly in an Australasian cohort. We aimed to assess the efficacy and safety of MTX in childhood AA based on our institutional experience. Methods: A retrospective chart review was performed from patients treated by a consultant dermatologist. Consecutive children with AA treated with MTX seen between 2010 and 2019 were analysed. A meta‐analysis of proportions was conducted for response rates, recurrences and complications of reported data in the literature. Results: Overall, 7 cases (70%) achieved treatment success whilst on MTX treatment. The remainder of cases were considered treatment failures. These were three children with partial regrowth with persistent patches on the scalp. No serious side effects were reported. Two cases experienced nausea or vomiting after MTX administration which was transient. Pooled meta‐analysis showed success rates of 49.7%, recurrences in 30% and side effects in 15.7% of cases. Conclusions: Overall, this study shows that methotrexate for paediatric AA in an Australian context was beneficial for the majority of cases assessed and had minimal adverse effects. We propose that such treatment should not be ruled out in the paediatric population.